SISTEM PIDANA DI INDONESIA: DASAR HUKUM, PENERAPAN, DAN TANTANGANNYA - Rafni Narti; Riri Syafitri; Yudi Krismen (STKIP Subang, 2026)
The criminal justice system in Indonesia is an integral part of the national legal system, which aims to maintain public order, protect the rights of citizens, and deliver justice. This journal discusses the legal foundations underpinning the criminal justice system in Indonesia, the mechanisms of its implementation in practice with an emphasis on the key differences between the New Criminal Code and the Old Criminal Code at every stage of the legal process, as well as the various challenges faced in the effort to achieve fair and effective law enforcement. This discussion also includes an overview of the latest developments in the formulation of criminal law in Indonesia as well as an analysis of a real-life case the sugar import corruption case involving Thomas Trikasih Lembong (Tom Lembong) up to the granting of a presidential pardon to provide a comprehensive picture of the legal process and the president’s special authority within the Indonesian legal system. The study’s findings indicate that legal reform through the New Criminal Code (KUHP) brings about a significant paradigm shift; however, its implementation still requires continuous improvement in human resources, infrastructure, and public understanding.